2014
DOI: 10.1002/adhm.201300641
|View full text |Cite
|
Sign up to set email alerts
|

A Size‐Exclusion Nanocellulose Filter Paper for Virus Removal

Abstract: This is the first time a 100% natural, unmodified nanofibrous polymer‐based membrane is demonstrated capable of removing viruses solely based on the size‐exclusion principle, with a log10 reduction value (LRV) ≥ 6.3 as limited by the assay lower detection limit and the feed virus titre, thereby matching the performance of industrial synthetic polymer virus removal filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
134
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 34 publications
1
134
0
1
Order By: Relevance
“…It is clear that the major drawback of membranes produced by the Nano paper approach is their low presence (flux). Metreveli et al showed that cladophora nanocellulose-based filter paper can act as a size-exclusion membrane for the removal of relatively large viruses, with sizes >50 nm [91]. …”
Section: Nanocellulose-based Water Purification Membranes and Filtersmentioning
confidence: 99%
“…It is clear that the major drawback of membranes produced by the Nano paper approach is their low presence (flux). Metreveli et al showed that cladophora nanocellulose-based filter paper can act as a size-exclusion membrane for the removal of relatively large viruses, with sizes >50 nm [91]. …”
Section: Nanocellulose-based Water Purification Membranes and Filtersmentioning
confidence: 99%
“…Our group has made research efforts towards finding useful applications of Cladophora nanocellulose 2015;Metreveli et al 2014;Nyholm et al 2011;Razaq et al 2012). The use of Cladophora nanocellulose is well in line with the concept of sustainable industrial scale processing, as the source of this cellulose is abundant and, in addition, Cladophora algae are typically considered undesirable pollutants, known for forming large, foulsmelling, algal mats and having adverse effects on the aquatic ecosystem as well as harbouring bacterial pathogens (Mihranyan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The term nanocellulose fibers usually refers to fibers within a general size range of 10 nm to 1000 nm, basically consisting of nanocrystalline cellulose, nanofibrillated cellulose, and bacterial cellulose. Due to its excellent properties, such as thermal stability, environmental benefits, optical transparency, and hydroxyl groups on the surfaces, nanocellulose fibers have become a precursor in a variety of new functional biomaterials, including transparent films , aerogels (Chen et al 2014), reinforcing agents (Tibolla et al 2014), and separation membranes (Metreveli et al 2014).…”
Section: Introductionmentioning
confidence: 99%